Better Teaching and Learning (BTL) Model on Islamic Religious Education Lessons - Edi Saputra; Saiful Akhyar Lubis; Adlan Adlan (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study is to determine whether the BTL learning paradigm is feasible, legitimate, and effective in Islamic Religious Education sessions. The study population consisted of 48 students in grades VIII A and B at SMPN 7 Medan. This research method combines Research and Development and the ADDIE Model. The study's findings indicate that when compared to the conventional model, the BTL learning model in Islamic Religious Education sessions produces a practical BTL model. Following trials, the BTL learning model for Islamic Religious Education lectures resulted in a valid model and steps. After implementing the BTL learning model in Islamic Religious Education lessons for students in grades VIII A and B of SMPN 7 Medan, it was discovered that the processes from learning to development were beneficial.